2020
DOI: 10.3390/ijms21062121
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Cohort-Specific Zinc Signature Acquisition and Capacitation-Induced Zinc Flux Regulate Sperm-Oviduct and Sperm-Zona Pellucida Interactions

Abstract: Building on our recent discovery of the zinc signature phenomenon present in boar, bull, and human spermatozoa, we have further characterized the role of zinc ions in the spermatozoa’s pathway to fertilization. In boar, the zinc signature differed between the three major boar ejaculate fractions, the initial pre-rich, the sperm-rich, and the post-sperm-rich fraction. These differences set in the sperm ejaculatory sequence establish two major sperm cohorts with marked differences in their sperm capacitation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
(70 reference statements)
0
24
0
3
Order By: Relevance
“…Regarding the analysis of the PMI, we found that the spermatozoa with compromised plasma membrane were enriched in PTP at the equatorial region in every sample just right after thawing (before DGC) (Table 4, Figure 5). To our knowledge, this relationship has never been reported before and we hypothesize that it could indicate that these spermatozoa are at a late stage of capacitation as membrane becomes more fluid and permeable to vital stains such as shown for propidium iodide [50]. Another possibility is that capacitated spermatozoa, thus showing increased PTP, are more prone to enter in an apoptotic state and suffer membrane damage [26,27].…”
Section: Discussionmentioning
confidence: 66%
“…Regarding the analysis of the PMI, we found that the spermatozoa with compromised plasma membrane were enriched in PTP at the equatorial region in every sample just right after thawing (before DGC) (Table 4, Figure 5). To our knowledge, this relationship has never been reported before and we hypothesize that it could indicate that these spermatozoa are at a late stage of capacitation as membrane becomes more fluid and permeable to vital stains such as shown for propidium iodide [50]. Another possibility is that capacitated spermatozoa, thus showing increased PTP, are more prone to enter in an apoptotic state and suffer membrane damage [26,27].…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, zinc blocking of HVCN1 channels in capacitated human sperm reduces progesterone-induced acrosomal exocytosis due to the inhibition of CatSper channels, which again underpins the close functional relationship between these two kinds of channels in this species [33]. In capacitated pig spermatozoa, SLO1 blockage also inhibits progesterone-induced acrosomal exocytosis by reducing Ca 2+ entrance to the sperm head [7], whereas the presence of zinc prevents acrosomal membrane modifications associated with acrosomal exocytosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…The significant changes observed in the architecture of the plasma membrane produced during capacitation, such as cholesterol removal, glycoprotein redistribution, and loss of phospholipid asymmetry [ 47 ], affects the lifespan of the spermatozoa, making them more vulnerable to damage. Thus, the plasma membrane of capacitated spermatozoa becomes more permeable to vital stains such as propidium iodide [ 48 ] and/or, as occurs with the acrosomal membrane, becomes more prone to destabilization [ 49 ]. This was likely more pronounced in our samples as we employed frozen/thawed spermatozoa, which are known to be more sensitive to the destabilizing conditions of capacitation, as the abundance of spermatozoa sustaining sublethal damage could be high.…”
Section: Discussionmentioning
confidence: 99%